If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -68 + -2x = 6x + 132 Reorder the terms: -68 + -2x = 132 + 6x Solving -68 + -2x = 132 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -68 + -2x + -6x = 132 + 6x + -6x Combine like terms: -2x + -6x = -8x -68 + -8x = 132 + 6x + -6x Combine like terms: 6x + -6x = 0 -68 + -8x = 132 + 0 -68 + -8x = 132 Add '68' to each side of the equation. -68 + 68 + -8x = 132 + 68 Combine like terms: -68 + 68 = 0 0 + -8x = 132 + 68 -8x = 132 + 68 Combine like terms: 132 + 68 = 200 -8x = 200 Divide each side by '-8'. x = -25 Simplifying x = -25
| 53=5x+11 | | x-20+4=1 | | 5x-23=4x-23 | | 12y-3=21 | | 2x-4x-11=-2x+4-11 | | 6+2y=18 | | 7r+2(3r+12)=63 | | 0.04(y-17)+0.08y=0.02y-0.01(70) | | 6c=4a+1c | | 9-(4y-7)=3-5y | | 2y-8=3x | | 14x-8+3x-4=13x-3+3x | | 2x+1.73=12 | | 0.30x+0.05(6-x)=0.10(-37) | | 6x+12x-8=16x-4-6 | | 2y-3x-8=0 | | 4(-2+5)=2(4x+5) | | 5r=6r+55 | | -4(t-3)-2(-7t-8)=9(t+2) | | 3x+2=x+11 | | -10+7x=x | | -185+9x=-4x+62 | | 7n+4-3n+5=6n-5+4n | | 56-x=x | | 4x-29=-x-4 | | -5a+6=-4a-7 | | 5(2-x)=x-17 | | -45-x=43-5x | | 3x+5=2-4(x+1) | | 13(4y-11)=7+5(11y+9) | | x-[9x-(x-8)]=0 | | 7x+17-9x=20-14x+12x-3 |